2020
DOI: 10.1177/1558866120964818
|View full text |Cite
|
Sign up to set email alerts
|

Recreate and Retain: How Entrance Into a Campus Recreation Facility Impacts Retention

Abstract: This study explored the rates of retention among students who entered a campus recreation facility. The purpose of the study was to determine the statistical significance of the rates of retention within several commonly studied demographic categories. Recent research in the field reported that student participation in campus recreation programs contributes to student retention. The researchers in this study also sought to determine whether there was a significant impact on campus recreation participants to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Prior studies have noted that university administrators and student affairs professionals have begun to formally recognize the impact of campus recreation activities on the retention of students ( Miller, 2011 ; Milton et al, 2020 ). However, no other studies have been conducted to determine whether campus recreation centers continue to influence student return or retention during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have noted that university administrators and student affairs professionals have begun to formally recognize the impact of campus recreation activities on the retention of students ( Miller, 2011 ; Milton et al, 2020 ). However, no other studies have been conducted to determine whether campus recreation centers continue to influence student return or retention during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that student involvement in recreation center activities motivate students to return and remain at college campuses ( Miller, 2011 ; Milton et al, 2020 ). However, during these uncertain times, many students are apprehensive about returning to a university campus due to the COVID-19 pandemic.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…According to the equivalent media theory (theory of composite properties), the structural unit of new energy materials is a subwavelength size smaller than its working wavelength, so they can be regarded as a whole. Moreover, their electromagnetic characteristics can be expressed by the equivalent permeability Ueff and equivalent dielectric constant Eeff [20].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, research on the benefits of recreational centers has proliferated over the last two decades. Researchers have discovered that college students’ participation in recreational centers, intramural sports, outdoor recreation, and fitness classes are directly and indirectly associated with increases in students’ leadership development (Dugan et al, 2014), academic performance (Vasold et al, 2019), retention (Miller, 2011; Milton et al, 2020), and physical health, mental health, and wellbeing (Wilson & Millar, 2021). Further, students who engage in recreational activities benefit from increased social connections and social bonds, an enhanced sense of belonging (feeling accepted, welcome, and valued in a college or university), and greater resilience (the ability to bounce back after adversity) (Henchy, 2011; Miller, 2011; Milton et al, 2020; St.…”
mentioning
confidence: 99%